Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0022103.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Aspects of Annelid Regeneration

Abstract: Annelids, like many other invertebrate animals, replace lost body parts in a process called regeneration. However, the ability to regenerate lost segments is present in some groups and not others; for example, leeches do not regenerate lost segments. Anterior and posterior regeneration involves the formation of a bud containing stem cells that differentiate into the new head or tail segments. Annelid regeneration also involves remodelling of surviving body fragments. The ability of annelids to regenerate tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Recently, Nino et al, 2016 demonstrated that during the anterior regeneration in the brain amputated earthworm Eudrilus eugeniae the nerve cord takes control of the neurological activities and regulates the segmental nerves to assist in worm's survival [7] . The process of regeneration in annelids is a combinatorial outcome of epimorphosis and morphallaxis and the formation of blastema during epimorphosis is supported by the neoblast stem cells residing particularly in the epidermal cell layers [103] , [104] , [105] . Especially the post amputation and wound healing process enables the synthesis and activation of several growth factors and signaling molecules, which assist in signal transduction by triggering the stem cell proliferation to facilitate the process of tissue regeneration and organogenesis [106] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Nino et al, 2016 demonstrated that during the anterior regeneration in the brain amputated earthworm Eudrilus eugeniae the nerve cord takes control of the neurological activities and regulates the segmental nerves to assist in worm's survival [7] . The process of regeneration in annelids is a combinatorial outcome of epimorphosis and morphallaxis and the formation of blastema during epimorphosis is supported by the neoblast stem cells residing particularly in the epidermal cell layers [103] , [104] , [105] . Especially the post amputation and wound healing process enables the synthesis and activation of several growth factors and signaling molecules, which assist in signal transduction by triggering the stem cell proliferation to facilitate the process of tissue regeneration and organogenesis [106] .…”
Section: Resultsmentioning
confidence: 99%
“…In annelids, work on marine naidine annelids has yielded that the position and developmental stage of amputations made, can ‘naturally’ rescue regenerative capacities[ 34 ]. The ability to regenerate anterior segments has been lost at least 12 times while the posterior regenerative ability was lost at least 4 times during the evolution of annelids [ 53 ]. The genome of E .…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of regeneration, in ammation and apoptosis factors launch the downstream process of development [41,42]. All of them were reported to play important roles in early embryonic development which contained several genes playing integral roles in re-speci cation of regenerated structures in several annelid species [14]. Due to the scarcity of annelid genomic data used for annotation, a large set of potentially novel DEGs in O.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, dozens of studies have proven that almost each species of annelids owns segmental regeneration ability which made it to be an excellent group to study the regeneration mechanisms [12,13]. The ability to regenerate segments in annelids after amputation varies from one species to another; however, anterior regeneration is less common than posterior regeneration which has been documented in many annelid groups [12,14]. In Ophryotrocha, no evidence has been shown for the ability of anterior regeneration, although species such as Ophryotrocha puerilis and O. notoglandulata have been shown to regenerate posteriorly [15].…”
mentioning
confidence: 99%